Bocheński’s Minima Moralia - Świderski, Edward M. (Filozofia Nauki, 2022)
Late in life, Józef Maria Bocheński set out to examine the age-old preoccupation with the question “how to live as well and as long as possible?” A traditional answer has been, “live wisely.” In his Handbook of Worldly Wisdom (2020), Bocheński analyzes this answer arguing that, conceptually, living wisely is distinct from obeying moral commandments, prescribing ethical rules, and recognizing authority (e.g., piety, free submission to divine authority). He claims that ethics consists solely in what moral philosophers label as “metaethics” — a theoretical discipline interested in the conceptual status of moral discourse qua discourse. However, Bocheński remains silent about a substantive ethics — that is, how a life led one way or another subscribes to some guiding value-set. As regards wisdom, therefore, the consequence of this position is that Bocheński’s account is ethically neutral. I argue that such a position entails a tension and dichotomy between, on the one hand, prudential rationality concerned with getting on in the moment — that is, wisdom — and, on the other hand, unconditional moral commandments. For his part, Bocheński does not recommend living according to wisdom’s precepts as he analyses them; his own path through life, he tells us, has been a commitment to Christian values, piety abetted by observance of moral commandments, a perspective that, I submit, is not ethically neutral: on the contrary, it entails thick, substantive value-choice. Bocheński’s avowal suggests a second dichotomy and tension, that between the worldly conduct of life, with moderate acknowledgment of moral principles, and an extra-worldly perspective (the “folly of the Cross”). Bocheński does not attempt to resolve either dichotomy, to seek a possible point of their convergence and integration, for instance by inquiring into moral psychology (i.e., the construction of self, the nature of the will, etc.). I believe that this set of views stems from conclusions Bocheński reached in advance of producing the Handbook that bear on, first, how philosophy should be conducted — as logical analysis hostile to grandiloquent speculation and synthesis (“worldviews”); and second, his utter dismissal as nefarious of anthropocentric views. Indeed, Bocheński asserts, without a blush, that almost everything “we” have come to believe about ourselves is superstition writ large. I trace what I consider to be difficulties with Bocheński’s account of wisdom — in relation to his take on morality, (meta-)ethics, and piety — to these idiosyncratic views.